Comparative study on bread quality and starch digestibility of normal and waxy wheat (Triticum aestivum L.) modified by maltohexaose producing α-amylases. (December 2022) - Yang, Tao; Zhong, Lingli; Jiang, Guangshuai; Liu, Lin; Wang, Pei; Zhong, Yingxin; Yue, Qianru; Ouyang, Lei; Zhang, Anqiang; Li, Zhoukun; Cui, Zhongli; Jiang, Dong; et al.
Graphical abstract: Highlights: α-Amylase plays an essential role in determining bread texture and in-vitro digestibility. The family 20 carbohydrate-binding module in α-amylase was explored. Normal and waxy wheats were used to differentiate the starch degradation by α-amylase. Abstract: It is highly desirable to produce bread with both acceptable texture and health benefits. In this study, maltohexaose (G6) producing amylase AmyM and its truncation AmyM-TR2 from Corallococcus sp. strain EGB were used to determine their effects to bread quality and starch physicochemical properties. During bread fermentation, AmyM or AmyM-TR2 continuously degraded the starch, resulting in more obvious decrease in relative crystallinity, the ordered structure, pasting viscosities and gelatinization enthalpy of starch than in control. The dough treated with AmyM or AmyM-TR2 increased bread volume and slowly digestible starch content, decreased bread hardness, and extended bread shelf life and as compared with control, and the dough treated with AmyM-TR2 had better improvement effects than AmyM. The volume and slowly digestible starch content of bread from the treatment of AmyM-TR2 increased by 9.74% and 7.56% in normal wheat, 1.42% and 10.28% in waxy wheat as compared with AmyM, respectively. AmyM-TR2 affected the substrate targeting, proximity and structure disruption effects, which contributed to the degradation of more starch than AmyM.